2020
DOI: 10.1177/0091217420946240
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to utilization of medications for opioid use disorder in primary care in South Carolina

Abstract: Objective Utilization of medications for opioid use disorder (MOUD) has not been widely adopted by primary care providers. This study sought to identify interprofessional barriers and facilitators for use of MOUD (specifically naltrexone and buprenorphine) among current and future primary care providers in a southeastern academic center in South Carolina. Method Faculty, residents, and students within family medicine, internal medicine, and a physician assistant program participated in focus group interviews, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…11,17,18 Many providers also echo the belief that MOUD is "just another drug." 19,20 Further, primary care physicians expressed concern that providing buprenorphine would "open the floodgates" to people with OUD, who were "difficult patients" and likely to be non-adherent or divert medications to non-prescribed uses or the street economy. 19 Research has suggested that exaggerated and unfounded fears of diversion have negatively affected office-based buprenorphine treatment.…”
Section: Substance Abuse: Research and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…11,17,18 Many providers also echo the belief that MOUD is "just another drug." 19,20 Further, primary care physicians expressed concern that providing buprenorphine would "open the floodgates" to people with OUD, who were "difficult patients" and likely to be non-adherent or divert medications to non-prescribed uses or the street economy. 19 Research has suggested that exaggerated and unfounded fears of diversion have negatively affected office-based buprenorphine treatment.…”
Section: Substance Abuse: Research and Treatmentmentioning
confidence: 99%
“…For example, research has shown that many people with OUDs are opposed to starting MOUD, feeling that it is “just another drug” or “replacing one drug for another,” an opinion echoed by many in the public and in 12-step groups. 11 , 17 , 18 Many providers also echo the belief that MOUD is “just another drug.” 19 , 20 Further, primary care physicians expressed concern that providing buprenorphine would “open the floodgates” to people with OUD, who were “difficult patients” and likely to be non-adherent or divert medications to non-prescribed uses or the street economy. 19 Research has suggested that exaggerated and unfounded fears of diversion have negatively affected office-based buprenorphine treatment.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Provider concerns about "opening the flood gates" to OUD patients and beliefs about the usefulness of MOUD have also been identified as barriers. 12,[16][17][18] Multiple studies have reported stigma among healthcare providers against patients struggling with substance use disorder, which accounts for the hesitancy in prescribing MOUD. [19][20][21][22] It is unclear if the recent removal of the buprenorphine waiver training requirement has changed attitudes toward some of these perceived barriers, especially among primary care providers who are at the forefront of the opioid epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…(While Medications to treat Opioid Use Disorder, MOUD, are now the preferred nomenclature for this class of treatment, MAT is still the most commonly used term in Uganda, so we will use MAT throughout the paper to avoid confusion.) However, even though both methadone and buprenorphine have been used for many decades in many countries such as the US, there is still a considerable amount of stigma regarding MOUD, which is amplified by tight regulations over its use [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Tanzania and Kenya recently opened methadone clinics in 2016 and 2018, respectively [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%